2012
DOI: 10.1124/jpet.112.197871
|View full text |Cite
|
Sign up to set email alerts
|

The Antinociceptive Effects of Nicotinic Receptors α7-Positive Allosteric Modulators in Murine Acute and Tonic Pain Models

Abstract: The a7 nicotinic acetylcholine receptor (nAChR) subtype is abundantly expressed in the central nervous system and in the periphery. Recent evidence suggests that a7 nAChR subtypes, which can be activated by an endogenous cholinergic tone, comprising acetylcholine and the a7 nAChR agonist choline, play an important role in subchronic pain and inflammation. This study's objective was to test whether a7 nAChR positive allosteric modulators (PAMs) produce antinociception in in vivo mouse models of acute and persis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
76
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(80 citation statements)
references
References 54 publications
4
76
0
Order By: Relevance
“…Additional results using type I (e.g., NS1738) and type II (e.g., PNU-120596) PAMs also indicate that α7 PAMs do not produce unspecific stimulation (Freitas et al, 2013a(Freitas et al, , 2013b. The current results indicate that co-administration of nicotine and PAM-2 also induces antidepressant-like activity.…”
Section: Discussionsupporting
confidence: 60%
“…Additional results using type I (e.g., NS1738) and type II (e.g., PNU-120596) PAMs also indicate that α7 PAMs do not produce unspecific stimulation (Freitas et al, 2013a(Freitas et al, , 2013b. The current results indicate that co-administration of nicotine and PAM-2 also induces antidepressant-like activity.…”
Section: Discussionsupporting
confidence: 60%
“…Some recent studies (Freitas et al, 2013) demonstrating analgetic effects of PNU-120596 suggest that this may be the case. However, the ubiquitous presence of choline in all in vivo and most in vitro experiments makes it impossible to conclude that such effects are due to the activity of the PAM alone.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, PNU-120596 induced analgesic activity by its own or combined with choline in the formalin pain test, and showed anti-allodynic effects in the CCI neuropathic pain model [33][34][35]. On the other hand, it is reported that different dietary polyphenols, like chlorogenic acid (CGA), resveratrol and quercetin derivatives, have antinociceptive effects on acute, inflammatory and neuropathic pain models [36][37][38], although their mechanisms of action are not totally understood.…”
Section: Analgesic Activitymentioning
confidence: 97%